2005
DOI: 10.1590/s1519-566x2005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Foraging patterns in a nocturnal swarm-founding wasp, Apoica flavissima van der Vecht (Hymenoptera: Vespidae)

Abstract: Padrões de Forrageamento na Vespa Noturna Apoica flavissima van der Vecht (Hymenoptera: Vespidae) RESUMO -O comportamento de forragear é fundamental para o desenvolvimento das colônias de insetos sociais, pois permite que as colônias sejam supridas de alimento, água e materiais utilizados para a construção dos ninhos. Vespas sociais do gênero Apoica Lepeletier (Hymenoptera: Vespidae) têm comportamento de forrageamento noturno como uma de suas principais características, porém estudos sobre aspectos abióticos q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 2 publications
0
12
0
6
Order By: Relevance
“…When light levels have risen (morning) or fallen (evening) to precisely the right intensity, Megalopta emerges to forage (Warrant et al, 2004;Kelber et al, 2006). The nocturnal wasp Apoica also departs its nest at a specific time in the evening -in fact, hundreds of wasps depart en masse -and this too is almost certainly dependent on the light level (Hunt et al, 1995;Nascimento and Tannure-Nascimento, 2005). Although experimental evidence is lacking, the ocelli could play an important role in the timing of foraging in Apoica and Megalopta.…”
Section: Possible Roles For Nocturnal Ocelli In Rainforest Habitatsmentioning
confidence: 99%
“…When light levels have risen (morning) or fallen (evening) to precisely the right intensity, Megalopta emerges to forage (Warrant et al, 2004;Kelber et al, 2006). The nocturnal wasp Apoica also departs its nest at a specific time in the evening -in fact, hundreds of wasps depart en masse -and this too is almost certainly dependent on the light level (Hunt et al, 1995;Nascimento and Tannure-Nascimento, 2005). Although experimental evidence is lacking, the ocelli could play an important role in the timing of foraging in Apoica and Megalopta.…”
Section: Possible Roles For Nocturnal Ocelli In Rainforest Habitatsmentioning
confidence: 99%
“…Unfortunately we do not have physiological data of Polybia species, but such a high temperature will generally shorten the developmental period of brood. In addition, higher temperatures by extra-combs may infl uence the performance of adults under the cool environment, since the fl ight activity of wasps is closely related to the thermal environment (Heinrich 1984, Lima & Prezoto 2003, Nascimento & Nascimento 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Hunt and colleagues (Hunt et al, 1995) found that Apoica forages during the first 4 h of the evening when the moon is new or small, with another small peak of activity just before dawn (due to wasps returning to the nest, possibly because it was too dark to find their way home any earlier). As the moon waxes, Apoica also begins to forage all night (Hunt et al, 1995;Nascimento and Tannure-Nascimento, 2005).…”
Section: Nocturnality In Bees and Waspsmentioning
confidence: 99%